The Effect Of Marketing Affilliate Tiktok And Discount Prices On Purchasing Decisions In Durin Tonggal Village - Sembiring, Elfrida; Simangunsong, Sixson Roberto (SEAN Institute, 2024)
This final project discusses the effect of Tiktok Affiliate Marketing and Discount Prices on Purchasing Decisions in Durin Tonggal Village. Changes in consumer behavior in Durin village from offline shopping to online shopping during the COVID-19 pandemic are the background of this study. The method used is quantitative with data collection through questionnaires distributed to 50 respondents and in. The results showed that TikTok content marketing and mobile marketing have a significant influence on consumer purchasing decisions. It is known in table 4.23 above that it can be concluded that Marketing affiliate tiktok has t count -1.467 < from t table 2.011 with a significant 0.149> 0.05, so there is no significant influence between Marketing Affiliate Tiktok on purchasing decisions because the t-count is smaller than the t-table and the p value (Sig.) is greater than 0.05 while the discount price has a t-count: 4.658> t-table: 2.011 and Sig: < 0.001 < 0.05 then there is a significant influence between the Discount Price on Purchasing Decisions because the t-count is greater than the t-table and the p value (Sig.) is less than 0.05. The simple linear regression test shows that the Discount Price variable has a significant and positive influence on the Purchasing Decision variable. With a slope coefficient of 0.548 and a t-count value of 4.658 which is much greater than the t-table of 2.011 and a p-value <0.001, we can conclude that an increase in Discount Price will significantly increase consumer purchasing decisions, indicating a significant effect of the discount price on purchasing decisions. These findings demonstrate the importance of digital marketing strategies, particularly through the TikTok platform, in attracting interest and influencing consumer purchasing decisions. This research provides insights for marketers to optimize the use of social media in their marketing campaigns.